Electromyographic analysis of the upper lip in nose and mouth breathers - Michelle Santos Vianna-Lara; Paulo Henrique Ferreira Caria (Universidade Estadual de Campinas, 2016)
The purpose of this research was to compare the electromyographic (EMG) activity of the superior belly of orbicularis oris muscle between individuals with Class II Division 1 malocclusion, nose breathers (Group 1) and mouth breathers (Group 2), having as a comparative parameter a control group of individuals with clinically normal occlusion (Group 3). The EMG recordings were obtained in resting position and in 16 movements. A statistically significant difference between Groups 1 and 2 was observed during puffing out with flaccid cheeks, dispelling of the lips' angle and saliva deglutition; between Groups 1 and 3 during puffing out with flaccid cheeks, posterior right and left clenching and saliva deglutition; between 2 and 3 during posterior right and left clenching. According to the normalized data the malocclusion groups (Groups 1 and 2) have a similar muscle behavior but when they are compared with the normal occlusion group there was a statistically significant difference between them. It can be concluded that, for this sample, the breathing mode did not influence the muscular behavior of the subjects with Class II division 1 malocclusion and that subjects with normal occlusion have more competent lips than the ones with Class II division 1 malocclusion.